The reality and the rhetoric organisational sustainability reporting - Frost, Geoffrey R.; Jones, Stewart, 1964-; Lee, Philip John (Sydney University Press, 2013)
"The reality and the rhetoric examines the gap between the external reporting of four Australian organisations and their internal management practices and systems necessary to support comprehensive and reliable disclosure. The book finds evidence of a significant rift between the external rhetoric of sustainability and the internal management processes and culture. However, the book also finds that the rhetoric can be effective in driving real change internally, as organisations seek to close the gap between the reality and rhetoric of sustainability reporting"--Back cover.